The Influence of Promotion, Price, and Brand Image on Purchasing Decisions on Vivo Smartphone Products - Meishella Sismi Indah Rahayu; Bayu Kurniawan; Heri Prabowo (Value Management Research, 2024)
This study aims to examine the influence of promotion, price, and brand image on purchasing decisions for Vivo smartphone products. The research was conducted with a sample of 100 respondents, specifically students from PGRI University Semarang. The sampling technique employed in this study is non-probability sampling with a purposive sampling approach, targeting individuals who meet specific criteria. Data collection was carried out using questionnaires to gather information about respondents' perceptions of the variables studied. The analysis was performed using the SPSS software application, which facilitated the processing of quantitative data and the testing of hypotheses. The findings of this study reveal that promotion does not have a significant effect on purchasing decisions for Vivo smartphones. In contrast, price has a significant influence, indicating that consumers consider pricing as a critical factor when deciding to purchase Vivo products. Additionally, brand image also significantly affects purchasing decisions, highlighting the importance of maintaining a positive perception of the brand to attract potential buyers. These results suggest that while promotional activities may not directly impact purchasing decisions in this context, pricing strategies and brand positioning play a crucial role in influencing consumer behavior. This research provides valuable insights for marketers and business practitioners in the smartphone industry, emphasizing the need to focus on competitive pricing and strong brand image development to enhance purchasing decisions among the target market.